2020
DOI: 10.1016/j.jcot.2019.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Complications of total joint arthroplasty in solid organ transplant patients versus a large control group

Abstract: Background: Solid organ transplant patients are theoretically at increased risk for complications after total joint replacement due to immunosuppressive medication regimens and multiple medical comorbidities. There are a number of studies that report on outcomes of total joint arthroplasty (TJA) following solid organ transplant, however, the results are heterogeneous. This study evaluated the outcomes of TJA in solid organ transplant patients as compared to non-organ transplant controls at one academic medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…also found no difference in peri-operative complications comparing SOT patients and matched controls who underwent primary total joint arthroplasty. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…also found no difference in peri-operative complications comparing SOT patients and matched controls who underwent primary total joint arthroplasty. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report on rTHA in SOT patients which stratifies by all-cause aseptic indications and infection. Several authors have previously highlighted an increased mortality in septic vs aseptic revisions [ 21 , [33] , [34] , [35] ]. For both SOT and nontransplant patients, we found worse outcomes in patients undergoing revision for infection, including longer LOS, as well as higher rates of 90-day readmission and 90-day re-revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Investigators also suggested increased adiposity provides greater metabolic reserves for catabolic illnesses such as heart failure. 40 Given that cardiovascular disease is one of the leading causes of death in TKA patients at all time points, these physiological mechanisms may partly explain the obesity paradox, if observed at all in TKA patients. 16,20,21 However, it should be noted that the obesity paradox is not a linear trend, and that unfavorable outcomes following joint replacement exist at either end of the BMI spectrum to reveal a "U"-shaped relationship 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of systemic diseases such as Diabetes and Chronic kidney disease and outcomes in patients with solid organ transplant is important to realize in view of a burgeoning population of these subgroups of patients. 7 Metal on Metal (MoM) articulations spelt doom for the patients and a large number out of over a million articulations implanted worldwide are still in situ. Chang and Haddad 8 outline, in their work, the understanding of the aetiology, presentation and management strategies for these patients with an aim to optimize their clinical outcomes.…”
mentioning
confidence: 99%